Development of a quantitative multi-compound method for the detection of 14 nitrogen-rich adulterants by LC-MS/MS in food materials. Issue 11 (2nd November 2017) - Frank, Nancy; Bessaire, Thomas; Tarres, Adrienne; Goyon, Alexandre; Delatour, Thierry
ABSTRACT: The increasing number of food frauds using exogenous nitrogen-rich adulterants to artificially raise the protein content for economically motivated adulteration has demonstrated the need for a robust analytical methodology. This method should be applicable for quality control in operations covering a wide range of analyte concentrations to be able to analyse high levels as usually found in adulteration, as well as low levels due to contamination. The paper describes a LC-MS/MS method covering 14 nitrogen-rich adulterants using a simple and fast sample preparation based on dilution and clean-up by dispersive SPE. Quantification is carried out by isotopic dilution reaching LOQs of 0.05–0.20 mg/kg in a broad range of food matrices (infant formula, liquid milk, dairy ingredient, high protein meal, cereal, infant cereal, and meat/fish powder). Validation of seven commodity groups was performed according to SANCO 12571/2013, giving satisfactory results demonstrating the method's fitness for purpose at the validated range at contamination level. Method ruggedness was further assessed by transferring the developed method into another laboratory devoted to routine testing for quality control. Next to the method description, emphasis is placed on challenges and problems appearing during method development as well as validation. They are discussed in detail and solutions are provided.